Initial cloning and sequencing of hydHG, an operon homologous to ntrBC and regulating the labile hydrogenase activity in Escherichia coli K-12. - Stoker, K (1989)
To isolate genes from Escherichia coli which regulate the labile hydrogenase activity, a plasmid library was used to transform hydL mutants lacking the labile hydrogenase. A single type of gene, designated hydG, was isolated. This gene also partially restored the hydrogenase activity in hydF mutants (which are defective in all hydrogenase isoenzymes), although the low hydrogenase 1 and 2 levels were not induced. Therefore, hydG apparently regulates, specifically, the labile hydrogenase activity. Restoration of this latter activity in hydF mutants was accompanied by a proportional increase of the H2 uptake activity, suggesting a functional relationship. H2:fumarate oxidoreductase activity was not restored in complemented hydL mutants. These latter strains may therefore lack, in addition to the labile hydrogenase, a second component (provisionally designated component R), possibly an electron carrier coupling H2 oxidation to the anerobic respiratory chain. Sequence analysis showed an open reading frame of 1,314 base pairs for hydG. It was preceded by a ribosome-binding site but apparently lacked a promoter. Minicell experiments revealed a single polypeptide of approximately 50 kilodaltons. Comparison of the predicted amino acid sequence with a protein sequence data base revealed strong homology to NtrC from Klebsiella pneumoniae, a DNA-binding transcriptional activator. The 411 base pairs upstream from pHG40 contained a second open reading frame overlapping hydG by four bases. The deduced amino acid sequence showed considerable homology with the C-terminal part of NtrB. This sequence was therefore assumed to be part of a second gene, encoding the NtrB-like component, and was designated hydH. The labile hydrogenase activity in E. coli is apparently regulated by a multicomponent system analogous to the NtrB-NtrC system. This conclusion is in agreement with the results of Birkmann et al. (A. Birkmann, R. G. Sawers, and A. Böck, Mol. Gen. Genet. 210:535-542, 1987), who demonstrated ntrA dependence for the labile hydrogenase activity.